Digital economy, consumption structure and rural economic transformation: a case study of China - Yang Liu; Wenjuan Chen; Xu Zhang; Wenmei Liao; Wenmei Liao; Wenmei Liao (Frontiers in Sustainable Food Systems)
IntroductionPromoting rural economic transformation is an important foundation for achieving agricultural modernization. Under the background of rural revitalization strategy, digital technology is increasingly being applied in the agricultural sector, and the digital economy is becoming a new driving force for China's rural economic transformation.MethodsBased on China's provincial panel data from 2013 to 2020, this paper uses the two-way fixed effect model, intermediary effect model, and panel threshold model to deeply analyze the impact and internal mechanism of the digital economy development on rural economic transformation.Results and discussionThe research shows that the digital economy significantly promotes China's rural economic transformation, and this conclusion is still valid after robustness tests such as selecting historical data as instrumental variables. The mechanism test confirms that the digital economy promotes rural economic transformation by optimizing residents' consumption structure. In addition, the digital economy has a single threshold effect on the rural economic transformation based on the level of consumption structure. After crossing the threshold value, its promotion effect on the rural economic transformation is more prominent, indicating that the impact of the digital economy on the rural economic transformation will show the non-linear characteristics of increasing ‘marginal effect' due to the different levels of consumption structure; Heterogeneity analysis found that compared to southern regions, the digital economy in northern regions has a more significant promoting effect on rural economic transformation. This study deepens the understanding of the motivation for rural economic transformation and the effects, mechanisms, and regional differences of the digital economy empowering rural economic transformation. Based on this, this paper proposes that the government fully realize the digital economy's important role in rural economic transformation, actively innovate and promote digital technology, continue to expand and strengthen the consumer Internet, adjust measures to local conditions, and try to achieve coordinated development.